Pengaruh Pemberian Posisi Head Up 30° Terhadap Tingkat Kenyamanan Pasien Cedera Kepala Di Ruang Instalasi Gawat Darurat RSUD Tidar Kota Magelang: Case Report - Muh. Ihya Alimuddin; Al-Afik; Cipto Wahyuning Utama (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Head injury is a pathophysiological event that occurs after trauma to the head which can cover every part of the head consisting of the scalp, bones and brain tissue or all the organs in the head. Objective: To determine the effect of providing Head Up 30⁰ position on the comfort level of head injury patients. Method: The method in this research is to use a case report with the nursing intervention of providing a Head Up 30⁰ position to the comfort level of head injured patients, carried out for 4 observations every 15 minutes. Results: From the results of the research, nursing intervention was carried out, namely by providing Head Up 30⁰ position for 4 observations every 15 minutes. The results showed that there was a change in comfort level before and after Head Up 30⁰ position was carried out. Conclusion: Based on the results of research conducted by researchers regarding the effect of providing Head Up 30⁰ position on the comfort level of head injury patients in instalation emergency RSUD Tidar, Magelang City obtained from the results of case study research through intervention, it can be concluded that Head Up 30⁰ therapy has an effect on changes. comfort level of mild to moderate head injury patients with changes in oxygen saturation values increasing, intracranial pressure decreasing, and pain scale decreasing.